Decentering social theory - Go, Julian 1970- (Emerald, 2013)
Social theory and research has long faced the limitations of its conventional Eurocentric focus. The essays in this volume offer new thoughts and empirical studies for transcending those limitations. A continuation of PPSTs previous volume on "postcolonial sociology", this volume, "Decentering social theory," questions old categories, advances new postcolonial themes in social science, and debates alternative theoretical paradigms. The "scholarly controversies" section contains a critical exchange on "southern theory" between Raewyn Connell and Patricia Hill Collins, Mustafa Emirbayer, Raka Ray and Isaac Ariail Reed.
Includes index.